LOCAL WISDOM APPROACH IN REGIONAL AUTONOMY AS AN EFFORT TO PREVENT RELIGIOUS CONFLICT IN LOMBOK TENGAH, NUSA TENGGARA BARAT: --- - Dwi Indah Kartika (Humanities, Society, and Community, 2025)
Indonesia is an archipelagic country that has a diversity of traditions, languages, religions, cultures, and others. West Nusa Tenggara, one of the provinces in Indonesia also has a diversity of religions, traditions, and cultures. Central Lombok, has quite significant religious diversity, where Muslims are the majority of adherents of Islam among minorities, such as Christians, Catholics, Hindus, Buddhists, and Confucians, as well as adherents of other beliefs. However, the achievement of the tolerance index there over the past five years has been high, ranging from 3.5 - 3.7. Even so, the potential for inter-religious conflict still exists in Central Lombok. The problems of this study: (1) What factors trigger inter-religious disintegration in Central Lombok, West Nusa Tenggara? (2) How does the current regional autonomy policy in Central Lombok accommodate local wisdom as a preventive strategy for inter-religious conflict? (3) What is an effective approach model in integrating local wisdom into regional autonomy policy to prevent inter-religious conflict in Central Lombok, West Nusa Tenggara. The purpose of this study is to identify and analyze the factors that trigger inter-religious disintegration in Central Lombok, West Nusa Tenggara, analyze and review the current regional autonomy policy in Central Lombok in accommodating local wisdom as a preventive strategy for religious conflict, and formulate an effective approach model in integrating local wisdom into regional autonomy policy to prevent inter-religious conflict in Central Lombok, West Nusa Tenggara. Data collection techniques use observation, in-depth interviews, SLR, and documentation. The collected data will be processed using SLR. The objectives of this study are to map the main factors causing inter-religious disintegration there, to compile an in-depth analysis of regional autonomy policies in Central Lombok related to the accommodation of local wisdom, and to recommend a local wisdom-based approach model that can be effectively integrated into regional autonomy policies to prevent inter-religious conflict in Central Lombok, West Nusa Tenggara.